(3GdGbJUGO GdGSdGej OQGSI h JWHjbs - (3GHQGgje aGVd(B, (3GdOHhs ((3YeGf(B:s (3OGQ GdefGgL ddfTQ(B,s, 2008)
(3YGdL GdcJGH GdehVhY aj aUdjf QFjSjf JfGhd GdChd efgeG OGQSI aj GdEbJUGO GdCSdGej MjK LGAJ aj NeSI eHGMK JfGhd GdChd eaghe GdEbJUGO GdCSdGej ajeG JfGhd GdeHMK GdKGfj eUGOQ GdCbJUGO GdCSdGej hCQcGfI ajeG JfGhd GdeHMK GdKGdK GdJaQbI Hjf GdCbJUGO GdESdGej hHjf GdCbJUGOjGJ GdhVYjI ajeG JfGhd GdeHMK GdQGHY GdeTcdI GdCbJUGOjI hYdGLgG ef efXhQ CSdGej ajeG JfGhd GdeHMK GdNGeS hGdCNjQ CSHGH CgeGd JWHjb GdCbJUGO GdCSdGej hCKQI aj hGbY GdCeI (B. (3hLGA GdaUd GdKGfj eJfGhdG feGPL JWHjbjI ddCbJUGO GdCSdGej MjK LGA aj SJI eHGMK JfGhd GdeHMK GdChd ehba GdeDLQ ef JUQaGJ GdeSJCLQ ZjQ GdeTQhYI ajeG JfGhd GdeHMK GdKGfj GdeQGHMI ddBeQ HGdTQGA ajeG JfGhd GdeHMK GdKGdK GdHjY HGdJbSjW ajeG JfGhd GdeHMK GdQGHY ELQGA GdYbhO HhSGFd GdCJUGd GdMOjKI ajeG JfGhd GdeHMK GdNGeS GdEbGdI hCMcGegG aj GdTQjYI hGdbGfhf ajeG JfGhd GdeHMK GdSGOS GdCMcGe GdeJQJHI Ydi GdTQcI aj GdOjf OQGSI ebGQfI aj Gdabg GdESdGej hGdbGfhf GdeOfj(B.s
(3HjHdjhZQGajG U(B.285s
Keywords: (3GbJUGO GSdGejs; (3GdGbJUGO hGdGSdGes